PENGEMBANGAN BAHAN AJAR SMART DIGITAL BOOK “BELAJAR DAN PEMBELAJARAN”. - Nur Habibah; Diana Oktavia (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
One of the importance things that can increase the effectiveness of learning process is a textbook. the present of textbook that arranged based on students’ need can increase the effectiveness of learning process in the university. The aim of the research is to know is smart digital book “belajar dan pembelajaran” can be used for students?. This research is research and development (R&D) that used ADDIE (analysis, design, development, implementation and evaluation) model. The result of the research showed that smart digital book “belajar dan pembelajaran can be use for students in English education department. It can be shown form expert validation. It is 83,33 % for material expert and 76,66% for media expert.